Polygoni Multiflori Radix interferes with bile acid metabolism homeostasis by inhibiting Fxr transcription, leading to cholestasis - Dai, Yihang; Jia, Zhixin; Fang, Cong; Zhu, Meixia; Yan, Xiaoning; Zhang, Yinhuan; Wu, Hao; Feng, Menghan; Liu, Lirong; Huang, Beibei; Li, Yueting; Liu, Jie; et al. (Frontiers in Pharmacology, 2023)
Objective: To explore the possible mechanisms of cholestasis induced by Polygoni Multiflori Radix (PM). Methods: Low and high doses of water extract of PM were given to mice by gavage for 8 weeks. The serum biochemical indexes of aspartate aminotransferase (AST), alanine aminotransferase (ALT), glutamyltransferase (GGT) alkaline phosphatase (ALP) and so on were detected in the second, fourth, sixth, and eighth weeks after administration. At the end of the eighth week of administration, the bile acid metabolic profiles of liver and bile were screened by high-performance liquid chromatography tandem triple quadrupole mass spectrometry (HPLC-QQQ-MS/MS). Liver pathological changes were observed by hematoxylin and eosin staining. Real-time quantitative polymerase chain reaction (RT-qPCR) was used to detect the mRNA transcription of the target genes and Western blotting (WB) was used to the detect target protein expression. Results: Biochemical tests results showed the values of ALP and GGT were two and three times greater than the normal values respectively, and the value of R was less than 2. Histopathology also showed that PM caused lymphocyte infiltration, a small amount of hepatocyte necrosis and nuclear fragmentation in mouse liver. The proliferation of bile duct epithelial cells was observed in the high group. These results indicated that PM may lead to cholestatic liver injury. HPLC-QQQ-MS/MS analysis with the multivariate statistical analysis revealed significant alterations of individual bile acids in liver and gallbladder as compared to those of the control group. RT-qPCR showed that the transcription of Fxr, Shp, Bsep, Bacs, Mdr2, and Ugt1a1 were downregulated and that of Cyp7a1, Mrp3, and Cyp3a11 was significantly upregulated in the treatment group. WB demonstrated that PM also markedly downregulated the protein expression of FXR, BSEP, and MDR2, and upregulated CYP7A1. Conclusion: PM inhibited the expression of FXR, which reduced the expression of MDR2 and BSEP, leading to the obstruction of bile acids outflow, and increased the expression of CYP7A1, resulting in an increase of intrahepatic bile acid synthesis, which can lead to cholestasis.